Medienspezifische Schreibkompetenz. Forschungsdesiderate und didaktische Perspektiven - Lehnen, Katrin (My University, 2011)
The paper sketches recent developments in the research of writing and new media within school. Al-though new media are well established in everyday life and professional contexts, the German school system still does not provide overall concepts of media-specific reading and writing competencies. After discussing institutional preconditions, the paper presents didactic approaches which deal with different aspects of media-specific writing processes and strategies: electronic text-production, web-writing and e-learning platforms. Special attention is given to the potential of linguistic reasoning by the use of digital writing resources (e.g. collaborative writing in Wikis).
Keywords: Neue Medien; Computer; medienspezifisches Schreiben; digitale Schriftlichkeit; Webschriftlichkeit; Schreibkompetenzen; Schreibentwicklung; E-Learning; kollaboratives Schreiben; Wiki; Sprachreflex-ion; linguistisches Argumentieren und Begründen